Genome-Wide Association Study (GWAS) of dental caries in diverse populations - Rasha N. Alotaibi; Brian J. Howe; Jonathan M. Chernus; Nandita Mukhopadhyay; Carla Sanchez; Frederic W. B. Deleyiannis; Katherine Neiswanger; Carmencita Padilla; Fernando A. Poletta; Ieda M. Orioli; Carmen J. Buxó; Jacqueline T. Hecht; et al. (BMC, 2021)
Abstract Background Dental caries is one of the most common chronic diseases and is influenced by a complex interplay of genetic and environmental factors. Most previous genetic studies of caries have focused on identifying genes that contribute to dental caries in specific ethnic groups, usually of European descent. Methods The aim of this study is to conduct a genome-wide association study (GWAS) to identify associations affecting susceptibility to caries in a large multiethnic population from Argentina, the Philippines, Guatemala, Hungary, and the USA, originally recruited for studies of orofacial clefts (POFC, N = 3686). Ages of the participants ranged from 2 to 12 years for analysis of the primary dentition, and 18-60 years for analysis of the permanent dentition. For each participant, dental caries was assessed by counts of decayed and filled teeth (dft/DFT) and genetic variants (single nucleotide polymorphisms, SNPs) were genotyped or imputed across the entire genome. Caries was analyzed separately for the primary and permanent dentitions, with age, gender, and presence/absence of any type of OFC treated as covariates. Efficient Mixed-Model Association eXpedited (EMMAX) was used to test genetic association, while simultaneously accounting for relatedness and stratification. Results We identified several suggestive loci (5 × 10−8 < P < 5 × 10−6) within or near genes with plausible biological roles for dental caries, including a cluster of taste receptor genes (TAS2R38, TAS2R3, TAS2R4, TASR25) on chromosome 7 for the permanent dentition analysis, and DLX3 and DLX4 on chromosome 17 for the primary dentition analysis. Genome-wide significant results were seen with SNPs in the primary dentition only; however, none of the identified genes near these variants have known roles in cariogenesis. Conclusion The results of this study warrant further investigation and may lead to a better understanding of cariogenesis in diverse populations, and help to improve dental caries prediction, prevention, and/or treatment in future.